The Implementation of Theme Based Teaching to Improve Students’ Achievement in Narrative Text - Tussa’diah, H; Nurfadillah, K (KnE Social Sciences, 2018)
The research was aimed at finding out the improvement of the students’ reading achievement in narrative text by using Classroom Action Research. It was done through planning, action, observation, and reflection. Descriptive qualitative and quantitative design was applied to this research. The location of this research was SMP Tarbiyah Islamiyah Hamparan Perak, at Jl. Perintis Kemerdekaan Simpang Beringin Hamparan Perak of the academic year 2016-2017. The subject of this research was all students of VIII A class who consisted of 40 students. The objective was to find out the improvement of students’ achievement in narrative text by using Theme Based Teaching Approach. Based on the students’ reading score, students kept improving in every test. In the Pre-test, the mean score was 50.5. In the first cycle test, the mean of the students’ score was 69.25, and in the second cycle test, the mean score was 80.87. The improvement also could be seen from the number of the master students, in the Pre-test 0% students got point more than 75, in the first cycle test, 55% students got point more than 75, and in the second cycle, 100% students got point more than 75. The improvement was 45% from cycle I to cycle II. In other words, the students’ achievement in reading narrative text was improved, and based on the diary note, the observation sheet and the interview with the English teacher; it showed the expression and excitement of the students. They became more motivated in learning narrative text. Keywords: Narrative Text, Class Action Research, achievement